A U.S. Financial Conditions Index : Putting Credit Where Credit is Due - Swiston, Andrew (Washington, D.C. : International Monetary Fund, 2008)
This paper uses vector autoregressions and impulse-response functions to construct a U.S. financial conditions index (FCI). Credit availability-proxied by survey results on lending standards-is an important driver of the business cycle, accounting for over 20 percent of the typical contribution of financial factors to growth. A net tightening in lending standards of 20 percentage points reduces economic activity by 3/4 percent after one year and 1u percent after two years. Much of the impact of monetary policy on the economy also works through its effects on credit supply, which is evidence supporting the existence of a credit channel of monetary policy. Shocks to corporate bond yields, equity prices, and real exchange rates also contribute to fluctuations in the FCI. This FCI is an accurate predictor of real GDP growth, anticipating turning points in activity with a lead time of six to nine months. 15B.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet